Influence of anaesthetic technique on maternal and foetal outcome in category 1 caesarean sections – A prospective single-centre observational study - Chitra Rajeswari Thangaswamy (Indian Journal of Anaesthesia, 2018)
Background and Aims: In category 1 caesarean section (CS), there is limited evidence regarding superior anaesthetic technique. Hence, this study was designed to study the influence of anaesthetic technique on the maternal and foetal outcome. Methods: Patient characteristics, indication for CS, decision-to-delivery interval (DDI), uterine incision-to-delivery time (UIDT), cord blood pH, Apgar scores and neonatal and maternal outcome were noted. Composite endpoint (Apgar score <7, umbilical cord blood pH <7.2, neonatal intensive care unit admission or death) was created for adverse neonatal outcome. Logistic regression was done to assess the influence of confounding factors on the occurrence of adverse neonatal outcome. Results: Of 123 patients who underwent category 1 cesarean section, 114 patients were included for analysis. The DDI and UIDT were comparable. One and 5-min Apgar scores were significantly lower in the group general anaesthesia (GA) than in the group spinal anaesthesia (SA). The umbilical cord blood pH was comparable (7.21 ± 0.15 vs 7.25 ± 0.11 in groups GA and SA, respectively). Neonatal intensive care admission and maternal outcome were comparable in both the groups. Subgroup analysis of patients with foetal heart rate of less than 100 showed that group GA had significantly lower 1-min Apgar scores and umbilical cord blood pH and significantly more neonatal admission and mortality. Binominal logistic regression showed that group GA (odds ratio 2.9, 95% confidence intervals 1.27-6.41) and gestational age were independently associated with adverse neonatal outcome. Conclusion: GA for category 1 CS was associated with increased incidence of adverse neonatal outcome.